Depressive symptoms in South African black patients with Rheumatoid Arthritis - Pillay, Anersha (My University, 2012)
Background: Rheumatoid Arthritis (RA) is a chronic auto-immune musculoskeletal disorder of unknown aetiology that can result in physical disability, chronic pain and impaired quality of life. RA is associated with an increased prevalence of depression. The presence of depression in RA is reported to be associated with pain, functional disability, high disease activity and mortality. This study aims to determine the prevalence of depressive symptoms in a cohort of Black South African patients attending a Rheumatology outpatient clinic at a public health center. It also aims to determine the association and correlation between the presence of depressive symptoms and the sociodemographic profile and RA clinical characteristics of the study population. Methodology: The study was conducted in a Rheumatology out patient clinic. The study sample consisted of 100 systematically selected participants of Black race. The participants completed the disability questionnaire (HAQ-DI), Visual Analogue Scales (VAS) for pain, fatigue and disease activity; and the depression and tension subscales of the Arthritis Impact Measurement Scale (AIMS). The MADRS was then administered to assess depressive symptoms. Study participants were clinically assessed for disability, joint status and disease activity. Data was analyzed using the SAS version 9.1 statistical program. Results: The majority of the sample was female (85%) and unmarried (66%). The prevalence of current depression was 13.2%, although a further 22.2% of the sample was already stable on antidepressant treatment. The mean RA disease duration was 12.5 ± 9.2 years. No significant associations were found between the presence of depression and the sociodemographic variables. MADRS scores were significantly associated and correlated with disability (p = 0.002, r = 0.30); fatigue (p = <0.001, r = 0.43); disease activity (p = 0.001, r = 0.32); AIMS-D (p < 0.001, r = 0.40) and AIMS-T (p < 0.001, r = 0.35). Upon adjusting for age and clinical status, significant associations remained with MADRS scores and all five above-mentioned RA variables although correlations weakened slightly. Conclusions: Co morbid depression is prevalent in South African Black patients with RA. In order to improve clinical outcomes in RA, depression must be actively sought and effectively managed.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry Johannesburg, 2012
Keywords: Arthritis Rheumatoid; Depression; Pain--complications